Transition Factors to Low Carbon Community - Engagement Initiative for Slum Communities - Leknoi, Unruan (International Journal of Energy Economics and Policy, 2019)
Thailand has been classified as one of the ten countries that are at high risk for long-term climate change due to greenhouse gas emission, directly connected with the population size and urbanization. In 2019, Bangkok has 2,070 communities, one-third are slum communities with increasing greenhouse gas emissions. This research proposes a set of potential factors influencing community engagement initiatives to achieve a low carbon community in slum areas. The case studies on four slum communities in Bangkok by qualitative research found that the factors influencing the strength of engagement and the factors influencing the community motivation to achieve low carbon communities are still low. Consequently, this research provides new guidelines with four practical activities; (1) promoting the creation of an internal community network that can contribute to trust and positive social norms (2) promoting greenhouse gas emission reducing behaviors and adjusting attitudes toward climate change issues and (3) promoting proper relationships between the Bangkok Metropolitan Administration (BMA) and the communities. Keywords: Greenhouse Gas Emission, Slum Community, Community Engagement, Social Capital, Low Carbon Community JEL Classifications: Q54, Q56, Q58 DOI: https://doi.org/10.32479/ijeep.8370